Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Diabetes Mellitus Tipe II Diruang Interne RSUD Padang Pariaman - Muthia Putri Khairil; Mike Asmaria; Kheniva Diah Anggita; Aulia Asman (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Type II Diabetes Mellitus is a chronic disease characterized by hyperglycemia due to impaired insulin secretion or resistance. The International Diabetes Federation (IDF) reported that in 2021 there were 537 million people with diabetes in the world and is projected to increase to 643 million in 2030 and 783 million in 2045. At Padang Pariaman Regional Hospital, Type II Diabetes Mellitus cases are among the top 10 diseases with a total of 515 cases in 2023, increasing to 661 cases in 2024, and 567 cases in 2025. This study used a case study method on Type II Diabetes Mellitus patients in the Internal Room of Padang Pariaman Regional Hospital in 2026 with a nursing process approach. The results of the assessment on Mrs. S showed complaints of weakness, nausea, abdominal pain, decreased appetite, and a random blood sugar level of 259 mg/dl. Four nursing diagnoses were found, namely unstable blood glucose levels, acute pain, nausea, and risk of nutritional deficit. Interventions included blood glucose monitoring, hyperglycemia management, pain and nausea management, and nutritional needs. Conclusions indicate that comprehensive nursing care can improve patient conditions, characterized by lower blood glucose levels, fewer complaints, and increased appetite.